Design-Based Learning Activity and Self-Regulation in Education: A Review - Putra Habib Dhitareka; Riana Nurismawati; Amaira Utami (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Design-based learning has been widely recognized for its impact on the cognitive domain within educational settings. However, limited research has explored the interaction between design processes and students' self-regulation. This paper reviews 15 relevant studies to investigate the relationship between these two constructs. Findings suggest that design-based learning implemented through activities, projects, or problem-based tasks, fosters a complex, dynamic, and mutually reinforcing relationship with self-regulation. This interaction appears particularly robust in both science-oriented and art-related educational contexts. The review highlights overlapping cognitive and metacognitive elements that may influence this relationship. Further empirical research is needed to examine how self-regulation and design processes operate in practical pedagogical environments.